2022
DOI: 10.1111/cid.13105
|View full text |Cite
|
Sign up to set email alerts
|

Peri‐implant tissue health and patient satisfaction of vertical versus inclined posterior implants used to support overdentures with bar attachments. A one‐year randomized trial

Abstract: Introduction This study aimed to evaluate peri‐implant tissue health and patient satisfaction of vertical and inclined posterior implants for mandibular bar overdentures. Materials and methods Thirty edentulous participants received four implants in the interforaminal area of the mandible. The patients were randomly assigned into two equal groups; (1) vertical group (control): all implants were inserted vertically parallel to each other. Inclined group (study): the anterior implants were placed vertically, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(18 citation statements)
references
References 42 publications
(83 reference statements)
7
11
0
Order By: Relevance
“…48 The vertical group recorded significantly higher crestal bone loss than the angled group at T12. This was in agreement with a study by Ibrahim and colleagues 49 who reported that distally tilted posterior implants supporting mandibular overdentures showed less peri-implant bone loss compared to vertically placed implants. The tilting of posterior implants increased anteriorposterior spread and offered better and wider load distribution.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…48 The vertical group recorded significantly higher crestal bone loss than the angled group at T12. This was in agreement with a study by Ibrahim and colleagues 49 who reported that distally tilted posterior implants supporting mandibular overdentures showed less peri-implant bone loss compared to vertically placed implants. The tilting of posterior implants increased anteriorposterior spread and offered better and wider load distribution.…”
Section: Discussionsupporting
confidence: 93%
“…The increased gingival inflammation may cause increased gingival enlargement which could be responsible for increased pocket depth. This finding was in line with Elsyad and colleagues, 47 Elsyad and colleagues, 48 and Ibrahim and colleagues 49 who found an increase in PD with the advancement of time for patients wearing implant‐supported overdentures. However, no statistically significant difference was found in PD between groups at all observation times.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations